INCREASING TEACHERS’ ABILITY IN COMPILING LESSON PLAN BASED ON STRENGTHENING CHARACTER EDUCATION THROUGH THE WORKSHOP AT SMP N 1 BATU HAMPAR, BANTAYAN, KABUPATEN ROKAN HILIR - Lasmani (JEE (Journal of English Education), 2019)
This school action research aims to determine whether teachers' ability in compiling the lesson plan based on Strengthening Character Education can be increased through the workshop. This study uses a model developed by Chemish and Taggart noting every action or cycle always consists of four activities: (1) the action plan, (2) action, (3) observation, and (4) eflection.As preliminary data (before the workshop), the average score of teacher's ability was 73% with good category. Having held the workshop in the first cycle, the average score obtained is 98% with very good category. The research concludes that the workshop can increase the teachers’ ability in compiling the lesson plan (RPP) based PPK (Strengthening Character Education) at SMP Negeri 1 Batu Hampar.